Heralds of the Gospel wherever they are: Catholic permanent deacons on mission inter gentes - Scott, Callum David (Stellenbosch Theological Journal, 2023)
Jesus commands the Church to its reason for existence: preaching the Good News of salvation to all (Mt 28:18-20). For restoration in Christ, the magisterial theology of mission of the Catholic Church emphasises this mandate. The Vatican II document Ad Gentes restricts "missionaries" to "priests, Religious, or laymen" who are distinct from but are sent "to all". Deacons are excluded. As baptised and ordained Christians, permanent deacons are obliged to be missionary. However, they are usually incardinated into dioceses and are self-supporting, married men with familial and professional obligations. Thus, the possibilities for permanent deacons to be missionaries ad gentes are constrained. Ordained to be heralds of the Gospel, deacons may experience tension between the Gospel's demands and their lives. Argued from the Southern African "mission territory" context, it is contended that this existential tension can be overcome through an inter gentes missionary theology.